2018
DOI: 10.1021/acs.inorgchem.8b01617
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Two-Dimensional Thermal Expansion via Relaxation of Node Distortions

Abstract: The ability to tune physical properties is attractive for the development of new materials for myriad applications. Understanding and controlling the structural dynamics in complicated network structures like coordination polymers (CPs) is particularly challenging. We report a series of two-dimensional CPs [Mn(salen)][M(CN)]· xHO (M = Pt (1), PtI (2), and MnN (3)) incorporating zigzag cyano-network layers that display composition-dependent anisotropic thermal expansion properties. Variable-temperature single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 57 publications
1
29
1
Order By: Relevance
“…We note that the contractions of layers by FeMnN and FePt also influenced the accommodation of lattice waters into crystals. While our previous works [8a] indicated that MnMnN incoporated two lattice waters immediately after the synthesis, the single‐crystal analysis for FeMnN indicated no lattice water. In the case of FePt , although it was indicated that intralayer hollows surrounded by [Fe(salen)] + units have low residual electron densities, a specific occupancy of lattice water molecules could not be determined unlike MnPt that incorporates one lattice water.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…We note that the contractions of layers by FeMnN and FePt also influenced the accommodation of lattice waters into crystals. While our previous works [8a] indicated that MnMnN incoporated two lattice waters immediately after the synthesis, the single‐crystal analysis for FeMnN indicated no lattice water. In the case of FePt , although it was indicated that intralayer hollows surrounded by [Fe(salen)] + units have low residual electron densities, a specific occupancy of lattice water molecules could not be determined unlike MnPt that incorporates one lattice water.…”
Section: Resultsmentioning
confidence: 66%
“… (a) Temperture dependences of lattice constant changes relative to the 150 K values for FeMnN and MnMnN [8a] (left), and for FePt and MnPt [8a] (right). (b) Thermal variation in the angles between tetracyanometallate units in the zigzag layers of FeMnN and MnMnN (left), and of FePt and MnPt (right).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structures of the related heterometallic cyanido-bridged Mn-Pt-complexes [{Mn(salen)} 2 Pt(CN) 4 ] n (salen = N,N′-bis(salicylidene)ethylenediiminato) [5,6], [Mn(L)Pt(CN) 4 ] n (L = 2,13-dimethyl-3,12-diaza-6,9-dioxa-1(2,6)-pyridinacyclotridecaphane-2,12-diene) [7] and [Mn(phen) Pt(CN) 4 ] n (phen = 1,10-phenanthroline) [8] have been determined previously.…”
Section: Commentmentioning
confidence: 99%